Differences in external workload demand between session types and positions in collegiate men's ice hockey - Neeld, K.; Peterson, B.; Dietz, C.; Cappaert, T.; Alvar, B. (International Journal of Kinesiology & Sports Science, 2021)
Background: Despite the importance of using a thorough understanding of competition demands to optimize preparatory strategies, there is a paucity of longitudinal workload data in ice hockey. Objectives: The purpose of this study was to determine differences in workload characteristics between training and matches, and assess differences between forwards and defensemen. Methods: All players from a NCAA Division I Men`s Ice Hockey Team wore Catapult S5 units for all on-ice activities for two consecutive seasons. Seven workload variables (Player Load, Skating Load, Explosive Efforts, High Skate Load, Player Load·min-1, Skating Load·min-1, and Average Stride Force·lb-1) were used to quantify training and match workload characteristics. Results: Compared to training, matches resulted in significantly higher Player Load (p<0.001), Total Skating Load (p<0.001), Explosive Efforts (p<0.001), High Force Strides (p<0.001), and Average Stride Force·lb-1 (p=0.001), but training resulted in higher Player Load·min-1 (p<0.001) and Skating Load·min-1 (p<0.001). Compared to defensemen, forwards accumulated higher values in all seven workload measures, across all session types (p<.001). Conclusion: Matches required higher values in measures of intensity and volume, but lower work rate compared to training. Training had unique emphases based on when it occurred relative to the next match. Regardless of session type, forwards consistently produced higher workloads across all variables.